Analisis Nilai Penting Dalam Upaya Pelestarian Sumberdaya Arkeologi Di Kawasan Pangkalan Militer TNI AU Haluoleo Desa Ranomeeto Kabupaten Konawe Selatan - Sunarto Sunarto; syahrun syahrun (SANGIA JOURNAL OF ARCHAEOLOGY RESEARCH, 2017)
Archaeological resources in the Haluoleo Air Force Military Base region have a variety of remnantsof Japanese residence during the defense period in Kendari. But the threat of damage toarcheological resources is very potential due to natural factors andhuman factors. Thereforearchaeological resources must be carried out as soon as possible to prevent conservation frommore serious damage. The problem in this research is the inheritance of any archeologicalresources, what important valuesare contained in archeological resources, and what conservationefforts should be done. Archaeological resources in the Haluoleo Air Force Military Base area arebunkers, revetments, ammunition warehouses, and structures. Archaeological resources in theHaluoleo Military Air Force Base area contain important historical, scientific, cultural, educationaland economic values. Preservation of archeological resources in this area includes physical andlegal preservation. Physical preservation in the form of Adaptation, Restoration, Reconstruction,Rehabilitation, and Consolidation. While in terms of law, it is to provide legal legality toarcheological resources in the region.